Modal Verbs in Spoken and Written Text of BNC Sampler: Corpus-Based Study - Dindasari Sidabalok; Luthvia Chairunnisa; T. Silvana Sinar; Winda Ayuanda (LingPoet: Journal of Linguistics and Literary Research, 2023)
The purpose of this study is to find out which type of text between written and spoken text that has the highest frequency of modal usage. It analyzes the personal pronouns which be followed by modal verbs. This study employed a corpus linguistic method, relying on quantitative and qualitative techniques. In quantitative design, the researchers examined the frequencies of modal verbs used in spoken and written text. In the qualitative design, the researchers analyzed the functions of modal verbs in representing the expression shown from the text. The data source of this study is a corpus named BNC (British National Corpus) Sampler. The corpus has 184 texts with total amount of word tokens in all corpus texts is about two million. The result show the tendencies of spoken text are mostly to express permission, possibility, and ability. Meanwhile the written text mostly tends to express obligation, and necessity. Also there are similarities and differences between spoken text and written text. The similar finding is the personal pronoun that appears the most and the least are I and she. The different finding is the second most frequent pronoun which appears in spoken text is you, meanwhile in written text is it.